2012
DOI: 10.1107/s0021889812000337
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure phase transitions and equations of state in NiSi. I.Ab initiosimulations

Abstract: First-principles calculations have been used to determine the equation of state and structural properties of NiSi up to pressures equivalent to that in the Earth's inner core. At atmospheric pressure, the thermodynamically stable phase is that with the MnP structure (as found experimentally). At high pressures, NiSi shows phase transformations to a number of high-pressure polymorphs. For pressures greater than ∼250 GPa, the thermodynamically stable phase of NiSi is that with the CsCl structure, which persists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
73
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(84 citation statements)
references
References 48 publications
10
73
0
1
Order By: Relevance
“…More recently, a detailed experimental investigation of the NiSi phase diagram to ~65 GPa using both MAP and LHDAC techniques (Dobson et al 2016) determined the boundaries between the MnP, Pmmn, ε-FeSi and CsCl phases. In particular, the ε-FeSi to CsCl boundary was found to have a Clapeyron slope of -67 MPa/K, with the ε-FeSi + CsCl + liquid invariant point occurring at ~33 GPa and ~2125 K. (this study also found that, when the MnP-structured material is compressed at 300 K, a transition to a further metastable phase of NiSi occurs, somewhere between 35 and 60 GPa, with the high-pressure structure corresponding to that labelled Pnma-II by Vočadlo et al (2012) for which the transition was predicted to occur at ~42 GPa).…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…More recently, a detailed experimental investigation of the NiSi phase diagram to ~65 GPa using both MAP and LHDAC techniques (Dobson et al 2016) determined the boundaries between the MnP, Pmmn, ε-FeSi and CsCl phases. In particular, the ε-FeSi to CsCl boundary was found to have a Clapeyron slope of -67 MPa/K, with the ε-FeSi + CsCl + liquid invariant point occurring at ~33 GPa and ~2125 K. (this study also found that, when the MnP-structured material is compressed at 300 K, a transition to a further metastable phase of NiSi occurs, somewhere between 35 and 60 GPa, with the high-pressure structure corresponding to that labelled Pnma-II by Vočadlo et al (2012) for which the transition was predicted to occur at ~42 GPa).…”
mentioning
confidence: 55%
“…Stability of NiSi-structured phases in FeSi at 0 K Some of the stable NiSi structures seen in Vočadlo et al (2012) were a result of spontaneous transformations after relaxation of the starting structure. In order to replicate these calculations as closely as possible, the same starting structures have been used here, with the exception of the NiAs, 'anti'-NiAs and NaCl structures, which were all found to be unstable by a large margin in NiSi.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations